Utilizing big data paradigms for business intelligence - Darmont, Jérôme 1972-; Loudcher, Sabine (A volume in the Advances in business information systems and analytics (ABISA) book series, 2019)
"This book explores problems related to the five "Vs" of big data, technological issues, as well as big data analytics applications. It also covers how data must be extracted, grouped, organized, aggregated and correlated with methods and techniques such as data integration (ETL), data warehousing, online analytical processing (OLAP), reporting, data mining and machine learning"...